Biaxial elastic modulus of very thin diamond-like carbon (DLC) films - Chung, JW; Lee, CS; Ko, DH; Han, JH; Eun, KY; Lee, KR (ELSEVIER SCIENCE SA, 2001)
The biaxial elastic modulus of very thin diamond-like carbon (DLC) films was measured by the recently suggested free overhang method. The DLC films of thickness ranging from 33 to 1100 nm were deposited on Si wafers by radio frequency plasma-assisted chemical vapor deposition (r.f.-PACVD) or by the filtered vacuum arc (FVA) process. Because the substrate was partially removed to obtain sinusoidal free overhang of the DLC film, this method has an advantage over other methods in that the measured value is not affected by the mechanical properties of the substrate. This advantage is more significant for a very thin film deposited on a substrate with a large difference in mechanical properties. The measured biaxial elastic moduli were reasonable values as can be judged from the plane strain modulus of thick films measured by nanoindentation. The biaxial elastic modulus of the film deposited by r.f.-PACVD was 90 +/- 3 GPa and that of the film deposited by FVA process was 600 +/- 50 GPa. While the biaxial elastic modulus of the film deposited by FVA is independent of the film thickness, the film deposited by r.L-PACVD exhibited decreased elastic modulus with decreasing film thickness when the film is thinner than 500 nm. Although the reason for the different behavior could not be clarified at the present state, differences in structural evolution during the initial stage of film growth seem to be the reason. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: CONSTANTS; STRESS